Mclocks: Compact and high-performing microwave clocks for industrial applications - (:unkn) unknown (My University, 2025)
The Mclocks project aims to transfer recent advances in laboratory compact microwave atomic clocks towards new atomic clock instruments suitable for demanding industrial and technical applications in terms of frequency stability, size, power consumption and reliability. These new clocks shall show outstanding stability performances, i.e. fractional frequency stabilities (Allan deviation) of 10^-13 at 1s and in the 10^-15 range at one day time scale. One main goal of the project is the development of a pulsed optically pumped (POP) Rubidium (Rb) vapour cell frequency standard. The use of optical-microwave double-resonance spectroscopy by the time-domain Ramsey interrogation technique has been shown to be an efficient approach for the realisation of vapour-cell microwave atomic clocks with state-of-the art frequency stability. This pulsed optically pumped (POP) interrogation scheme allows detection of high-contrast, narrow-linewidth, and high signal-to-noise signals from a small (cm-size) thermal Rb vapour cell, as well as very small light-shift effects, which is very beneficial for the realization of the envisaged clock. In this project we investigate using a very compact (45 cm^3) magnetron-type microwave cavity for microwave interrogation of the atomic sample. This magnetron cavity has a three times smaller size than conventional fundamental-mode cavities and thus enables the realization of very compact POP clocks. A compact and frequency-stabilized laser head with switchable output laser power is under development in our group for this clock. This laser head and the new clock physics package based on the magnetron microwave cavity will be combined to form the core of a very compact and high-performance POP clock of high interest for future industrial or portable applications. The POP clock development is conducted in collaboration with the Istituto Nazionale di Ricerca Metrologica (INRIM, Italy). Two other types of clock are also developed within the Mclocks project and profit from contributions of the UniNE team: A Cs-cell CPT atomic clock, developed in collaboration with Observatoire de Paris / SYRTE and Université de Franche-Comté / FEMTO, and a Rb cold atom pulsed microwave atomic clock (Rubiclock) developed by Observatoire de Paris / SYRTE and MuQuans company (all in France). The Mclocks project is funded by the European Metrology Research Programme (EMRP, project IND55). The EMRP is jointly funded by the EMRP participating countries within EURAMET and the European Union.
Keywords: atomic clocks; microwave; frequency standards; industrial applications; metrology